2012
DOI: 10.1016/j.bcp.2012.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Nav types endogenously expressed in human SH-SY5Y neuroblastoma cells

Abstract: Abbreviations: Nav, voltage-gated sodium channel; TTX, tetrodotoxin; ProTxII, β/ω-theraphotoxin-Tp2a; Ca 2+ , calcium ion; DMEM, Dulbecco's Modified Eagle's Medium; FBS, foetal bovine serum; PBS, phosphate buffered saline; PSS, physiological salt solution; HBS, HEPES-buffered saline; AFU, arbitrary fluorescence unit; SEM, standard error of the mean; Fluo-4 AM, Fluo-4 acetoxymethylester; RPMI, Roswell Park Memorial Institute; BSA, bovine serum albumin; CCD, charge-coupled device; DAPI, 4',6-diamidino-2-phenylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 36 publications
10
98
0
Order By: Relevance
“…The inhibitory potency of HwTx-IV and two analogues on hNa V 1.7 was assessed using a calcium assay on a Fluorimetric Imaging Plate Reader (FLIPR TETRA ) assay as previously described [41]. SH-SY5Y cells expressing hNa V 1.7 were maintained in RPMI medium supplemented with 15% (v/v) fetal bovine serum (FBS), 100 units/mL penicillin, 100 units/mL streptomycin and 2 mM L-glutamine, with subculturing every 72 h (70-80% confluence).…”
Section: Inhibition Of Hna V 17 Induced By Hwtx-iv and Its Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory potency of HwTx-IV and two analogues on hNa V 1.7 was assessed using a calcium assay on a Fluorimetric Imaging Plate Reader (FLIPR TETRA ) assay as previously described [41]. SH-SY5Y cells expressing hNa V 1.7 were maintained in RPMI medium supplemented with 15% (v/v) fetal bovine serum (FBS), 100 units/mL penicillin, 100 units/mL streptomycin and 2 mM L-glutamine, with subculturing every 72 h (70-80% confluence).…”
Section: Inhibition Of Hna V 17 Induced By Hwtx-iv and Its Analoguesmentioning
confidence: 99%
“…Immediately prior to assays, media was removed and cells were washed in physiological salt solution (PSS: 140 mM NaCl, 11.5 mM glucose, 5.9 mM KCl, 1.4 mM MgCl 2 , 1.2 mM NaH 2 PO 4 , 5 mM NaHCO 3 , 1.8 mM CaCl 2 and 10 mM HEPES, pH 7.4). The SH-SY5Y cells were then incubated for 30 min at 37 °C with FLIPR calcium 4 dye, 30 nM of OD1 (a selective modulator of hNa V 1.7 inactivation), and 0.1% (w/v) bovine serum albumin (BSA) diluted in PSS buffer as previously described [41]. Peptides were prepared to achieve final concentrations ranging from 3 M to 1.7…”
Section: Inhibition Of Hna V 17 Induced By Hwtx-iv and Its Analoguesmentioning
confidence: 99%
“…Crude venom isolated from C. suturatus elicited increases in intracellular Ca 2þ that were associated with oscillations in SH-SY5Y cells and potentiated veratridine-induced Ca 2þ responses which are mediated through endogenously expressed hNa V 1.2, hNa V 1.3 and hNa V 1.7 [10]. Using assay-guided fractionation, we found that activity was associated with a single peak eluting at 63% B that was dominated by a single monoisotopic mass of A BLAST search using this sequence as a query revealed that Bt6.4, a superfamily O1 conotoxin isolated from the vermivorous Conus betulinus, was the closest homologue to this 27 residue long peptide (electronic supplementary material, figure S1), with 96% sequence identity (Asp .…”
Section: Results (A) Isolation Of a Novel Excitatory Conotoxin From Cmentioning
confidence: 95%
“…(b) Activity-guided isolation of SuVIA Activity-guided isolation of SuVIA was carried out using a FLIPR high-throughput Ca 2þ assay as previously described [9,10]. Briefly, the human neuroblastoma cell line SH-SY5Y (ATCC) endogenously expressing hNa V 1.2, hNa V 1.3 and hNa V 1.7 [10] was cultured in Roswell Park Memorial Institute (RPMI) medium containing 15% fetal bovine serum (FBS) and 2 mM L-glutamine and split every 3-4 days using 0.25% trypsin/EDTA (Life Technologies, Mulgrave, Victoria, Australia).…”
Section: Materials and Methods (A) Crude Venom Extraction And Fractionmentioning
confidence: 99%
See 1 more Smart Citation